2021
DOI: 10.3389/fcvm.2021.679599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Density Lipoprotein Cholesterol Goal Achievement on Vascular Physiology Evaluated by Quantitative Flow Ratio in Patients Who Underwent Percutaneous Coronary Intervention

Abstract: Purpose: The change in coronary physiology from lipid-lowering therapy (LLT) lacks an appropriate method of examination. Quantitative flow ratio (QFR) is a novel angiography-based approach allowing rapid assessment of coronary physiology. This study sought to determine the impact of low-density lipoprotein cholesterol (LDL-C) goal achievement on coronary physiology through QFR.Methods: Cases involving percutaneous coronary intervention (PCI) and 1-year angiographic follow-up were screened and assessed by QFR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Thus, we believe that it makes sense to track the coronary physiology by the QFR during follow up to further guide treatment strategies after revascularization. Finally, intensive glucose control, dyslipidemia management and early follow up might contribute to the improvement of coronary physiology in such patients 5 , 36 , 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we believe that it makes sense to track the coronary physiology by the QFR during follow up to further guide treatment strategies after revascularization. Finally, intensive glucose control, dyslipidemia management and early follow up might contribute to the improvement of coronary physiology in such patients 5 , 36 , 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent serial coronary CTA study by Yu et al [23], on the basis of 153 low-risk patients with mild to intermediate coronary stenosis, suggested that rosuvastatin treatment could improve hemodynamic status for non-calcified plaques assessed by lesion-specific CT-derived FFR. Another 2 recently published serial QFR studies showed that a close relationship exists between the on-treatment LDL cholesterol level and coronary functional progression as evaluated by per-vessel QFR in patients with residual stenosis after PCI [24,25]. These results support the benefits of intensive lipid-lowing therapies on atherosclerosis regression from a physiological aspect.…”
Section: Discussionmentioning
confidence: 71%
“…Additionally, Nozue et al [ 26 ] reported that DS was significantly determinant for coronary computed tomography angiography-derived fractional flow reserve (FFR CT ). Moreover, Chen et al [ 27 ] revealed, after adjusting, through QRF, the low-density lipoprotein cholesterol goal for coronary physiology, that the goal-achievement group exhibited lower DS with a better change in QFR and a lower incidence of major adverse cardiovascular events at 1-year follow-up [ 27 ]. Interestingly, our study’s DS follow-up was also lower in the LQ loss patients compared to their HQ loss counterparts.…”
Section: Discussionmentioning
confidence: 99%